The Grace of Distance : Poems - Thorburn, Matthew (Book collections on Project MUSE., 2020)
"A boy places a bell in the hollow of a tree, so someone might find it. An overworked baker wishes for an annunciation of her own. A man calls down into a well until another voice calls back. In this lonely, modern world, how do we close the distances between doubt and faith, between cultures, between ourselves and those we love? In his poignant, far-traveling new collection of poems, Matthew Thorburn seeks to name--and find--that elusive, essential sense of connection"--